2003
DOI: 10.1007/s11325-003-0177-6
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea in a Referral Population in India

Abstract: There are few published studies of obstructive sleep apnea in the Asian subcontinent. The objectives were to describe the syndrome and evaluate the utility of computed tomography (CT) cephalometry in patients found to have obstructive sleep apnea (OSA) by polysomnography. This article reports on a retrospective case series in a referral population. A total of 880 patients (560 males and 320 females) were seen in a referral center in Hyderabad, South India, during the last 7 years. All patients with suspected o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
2
3
3
Order By: Relevance
“…Our study reported a mean PSQI score of 6.70 ±3.32 which was more than that of a study conducted in Iran (5.5±4.4) [8] and lesser in comparison to the values reported by Vigg et al (8.3±4.6) [10]. The mean duration of sleep per night as reported by the study subjects (6.3±0.95 hours ) was slightly more than (6.10±166 hours) as reported by Vigg et al [10].…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Our study reported a mean PSQI score of 6.70 ±3.32 which was more than that of a study conducted in Iran (5.5±4.4) [8] and lesser in comparison to the values reported by Vigg et al (8.3±4.6) [10]. The mean duration of sleep per night as reported by the study subjects (6.3±0.95 hours ) was slightly more than (6.10±166 hours) as reported by Vigg et al [10].…”
Section: Discussioncontrasting
confidence: 84%
“…The result of the present study indicated that 57.3% of the subjects were classified as poor sleepers (PSQI> 5). The value obtained was higher compared to other studies conducted across the globe [8][9] which have reported 38 -48 % 0f their subjects as "poor sleepers" but lesser as compared to a similar study conducted in India by Vigg et al [10].…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The skeletal craniofacial morphology has also been shown to play a major etiological role in 62% of nonobese Asian OSA population as compared to soft-tissue morphology. 31 A meta-analysis by Miles et al 32 showed that among all the craniofacial risk variables, mandibular body length is the strongest risk factor exhibiting greater associations with OSA.…”
Section: Associative Relationships Between Malocclusion and Obstructive Sleep Apneamentioning
confidence: 99%
“…On the corollary, it is influenced by multiple factors such as physiological, psychological, environmental and sociocultural factors. In the recent past there has been an increase in awareness of normal sleep and sleep disorders in India 3,4,5 . The field, however, still remains in its infancy.…”
mentioning
confidence: 99%